Ticks of the Genus Rhipicephalus (Acari, Ixodidae) and Their Distribution in Ukraine - Akimov, I.A.; Nebogatkin, I.V. (Вестник зоологии, 2013)
Expansion of Rhipicephalus rossicus (Jakimov et Kohl-Jakimova, 1911) to the North, due to all its developmental stages have wide range of feeders (from amphibians to mammals) in the new man-made environmental conditions in the steppe and wood-and-steppe of Ukraine and the warming of climate (especially warm winters), is observed. The northern boundary of R. rossicus distribution lies in Vinnytsya, Kyiv, Poltava and Sumy Regions. R. bursa (Canestrini et Fanzago, 1878) and R. sanguineus (Latreille, 1806) occur only on the shores of the Black Sea and Sea of Azov (including the Crimea). Outbreak localities of R. sanguineus are in Kerch Peninsula (Crimea) and in the Dnieper floodplain. Both R. bursa and R. sanguineus are invasive species.